HUBUNGAN BERAT BADAN LAHIR DENGAN KEJADIAN STUNTING PADA ANAK USIA BALITA DI PUSKESMAS IDI TUNONG - Fuadi Fuadi; Isfanda Isfanda; Nazirah Nazirah (Jurnal Sains Riset, 2021)
Factors that influence stunting include low birth weight (LBW), lack of protein energy, chronic disease, insufficient food intake, poverty factors and inadequate parenting. The impacts include slow growth of children, low immunity, lack of intelligence and low productivity. This research aims to determine the relationship between birth weight and the incidence of stunting in children under five at Idi Tunong Health Center. This study used a descriptive correlative approach with a cross sectional design, the number of samples in this study amounted to 65 respondents using accidental sampling techniques, bivariate analysis using Chi-Square. The results showed that out of the 65 samples, 45 (66.7%) were born with normal weight and 20 (33.3%) were born with Low Birth Weight (LBW), of the 65 samples, 41 (63.1%) were stunted and 24 (36.9%) were not stunted. There is a significant relationship between birth weight and stunting in children under five at the Puskesmas Isi Tunong in 2020 (p 0.05). Based on the results of the study, it can be concluded that there is a significant relationship between birth weight and stunting in toddlers at the Puskesmas Isi Tunong in 2020. Finally, it is hoped that the head of the puskesmas will be able to provide input in developing a plan to socialize the prevention of stunting in toddlers.Keywords: Birth weigh, stunting, todler